2010
DOI: 10.1167/iovs.09-4933
|View full text |Cite
|
Sign up to set email alerts
|

Decorin Accumulation Contributes to the Stromal Opacities Found in Congenital Stromal Corneal Dystrophy

Abstract: Accumulation of decorin was found in the interlamellar areas of amorphous substance. The truncated decorin is present in CSCD corneas, and there is evidence it may aggregate in vitro. Thus, decorin accumulation appears to contribute to the stromal opacities that are characteristic of CSCD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 20 publications
0
24
0
Order By: Relevance
“…Three different frame-shift mutations (c.947delG; c.967delT; c.941delC) have been reported at the C-terminus of decorin; all of these deletion mutations lead to identical truncations of decorin, lacking a 33 amino acid segment that includes the SLRP-specific “ear” repeat (Bouhenni et al, 2011; Bredrup et al, 2010; Kim et al, 2011; Rodahl et al, 2006). Besides the deletion mutations, a family has been described with a decorin-associated CSCD involving a novel nucleotide substitution (c.1036T>G) within the C-terminus of decorin, which has resulted in a milder phenotype than in the truncated mutations (Lee et al, 2012).…”
Section: Corneal Stromal Diseasesmentioning
confidence: 99%
“…Three different frame-shift mutations (c.947delG; c.967delT; c.941delC) have been reported at the C-terminus of decorin; all of these deletion mutations lead to identical truncations of decorin, lacking a 33 amino acid segment that includes the SLRP-specific “ear” repeat (Bouhenni et al, 2011; Bredrup et al, 2010; Kim et al, 2011; Rodahl et al, 2006). Besides the deletion mutations, a family has been described with a decorin-associated CSCD involving a novel nucleotide substitution (c.1036T>G) within the C-terminus of decorin, which has resulted in a milder phenotype than in the truncated mutations (Lee et al, 2012).…”
Section: Corneal Stromal Diseasesmentioning
confidence: 99%
“…Increased amount of decorin, a small leucine rich proteoglycan that plays a pivotal role in modulating matrix assembly [134], was noted in corneas of cats with MPS VI [135]. It was also demonstrated that accumula tion of decorin contributes to corneal opacity [136]. Furthermore, expression of lens like crystallins (α, β, and γ crystallins) was noted in corneas of cats with MPS I and VI but not in normal corneas [137].…”
Section: Interruption Of Glycoprotein and Glycosaminoglycan Metabolismentioning
confidence: 99%
“…The reported mutations in DCN have all affected the C-terminus of the protein, including 3 deletions truncating the SLRP-specific "ear" repeat. [68][69][70][71] Mice heterozygous for mutant DCN recapitulated human CSCD, with corneal opacities and abnormal fibril organization, and disrupted normal expression of other SLRPs. 72 In vitro studies have shown that the aberrant DCN protein is retained within the ER, causing ER stress and consequently disrupting ECM component synthesis and assembly.…”
Section: Congenital Stromal Corneal Dystrophymentioning
confidence: 99%